Reaching the Unreached: School-on-the-air on Climate-Smart Agriculture (SOA-CSA) in Cagayan Valley - Navarro, Rex; Matalang, Rogelio P.; Tabbun, Hector U.; Sebastian, Leocadio S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
In 2018, the CGIAR Research Program on Climate Change, Agriculture and Food Security in Southeast Asia (CCAFS SEA) catalysed a collaborative radio-based distance learning project with the Philippine Department of Agriculture Regional Office 2 (DA- RFO2), Philippine Federation of Rural Broadcasters (PFRB), Philippine Agriculture Journalists, Inc. (PAJ) Cagayan Valley Chapter, Philippine Rice Research Institute (PhilRice) Isabela, Cagayan Valley Agriculture and Resources Research and Development (CVARRD) Consortium, and other regional agencies. The SOA was conducted from February to August 2018 and dubbed as “Kaalamang Pagsasaka sa Himpapawid: School-on-the-Air on Climate Smart Agriculture (SOA-CSA) in Cagayan Valley,” This working paper documents how the project harnessed the power of radio in sharing improved agriculture technologies and support services to a critical mass of farmers under climate change.